The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.newast.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Variable stars in Palomar 13; an evaporating globular cluster

Abstract: We present new CCD V I photometry of the distant globular cluster Pal 13. Fourier decomposition of the light curves of the three cluster member RRab stars lead to estimations of [Fe/H]=-1.65, and a distance of 23.67±0.57 kpc. Light and colour near minimum phases for RRab stars leads to an estimate of E(B − V)=0.104 ± 0.001. A V/(V − I) colour-magnitude diagram, built exclusively with likely star members, shows consistency with the above parameters and an age of 12 Gyrs. A search of variable stars in the field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 56 publications
2
18
1
Order By: Relevance
“…2, where it is evident that the whole cluster moves as a compact entity, and the stars in solidarity maintain their identity. This is contrary to what is seen for instance in Pal 13 (Yepez et al 2019) (their figure 12), a rather loose cluster being tidally disrupted. However, we note in the bottom panel of Fig.…”
Section: Comments On the Blue-straggler Population Of Ngc 6712contrasting
confidence: 84%
“…2, where it is evident that the whole cluster moves as a compact entity, and the stars in solidarity maintain their identity. This is contrary to what is seen for instance in Pal 13 (Yepez et al 2019) (their figure 12), a rather loose cluster being tidally disrupted. However, we note in the bottom panel of Fig.…”
Section: Comments On the Blue-straggler Population Of Ngc 6712contrasting
confidence: 84%
“…Balbinot & Gieles (2018) found that cluster tails are more densely packed at apogalacticon, so that the cluster should be in the best condition of tails (extra-tidal features) observability. From Baumgardt et al (2019), Pal 13 is currently at a Galactocentric distance of 25.92 kpc, so that is 1.5 times farther from its apogalactic distance than from its perigalactic one (see also the cluster's orbit in Yepez et al (2019)). At that position, the cluster exhibits a moderate extended halo of low density.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The method, originally developed to estimate distances to nearby galaxies (Lee et al ), has been used to corroborate the theoretical constrains that particle physics may impose on the extension of the RGB in globular clusters by comparing the predicted distance by the most luminous RGB with the results rendered by the RR Lyrae and SX Phe. Consistency between theoretical predictions and empirical calculations has been found for NGC 6229 by Arellano Ferro et al (), for M5 by Arellano Ferro et al (), and for NGC 6934 by Yepez et al . In brief, the bolometric absolute magnitude of the tip of the RGB was calibrated by Salaris & Cassisi () as: Mboltip=3.9490.178[]Mfalse/H+0.008M/H2, where [ M / H ] = [Fe/H] − log(0.638 f + 0.362), and log f = [ α /Fe], Salaris et al ().…”
Section: The Distance To Ngc 6362mentioning
confidence: 62%
“…The neat splitting of RRc and RRab stars is clear in Figure . This is significant given that, while the mode splitting has been found in all studied Oo II‐type clusters (nine so far) (Yepez et al ()), only some Oo I (three out of seven so far) have been observed. Figure , which is an updated version of fig.…”
Section: The Horizontal Branch Of Ngc 6362mentioning
confidence: 77%